Exosomes and SARS-CoV-2 infection - Li, Liuying; Yang, Zixuan; Li, Jia (Frontiers in Immunology, 2024)
Exosomes, which are small extracellular vesicles, are of particular interest in studies on SARS-CoV-2 infection because of their crucial role in intercellular communication. These vesicles are released by several cell types and are rich in “cargo” such as proteins, lipids, and nucleic acids, which are vital for regulating immune response and viral pathogenesis. Exosomes have been reported to be involved in viral transmission, immune escape mechanisms, and illness development in SARS-CoV-2 infection. This review examines the current research on the contribution of exosomes to the interplay between the virus and host cells, highlighting their potential as diagnostic biomarkers and therapeutic targets in combating COVID-19.